Rehabilitation with complete prothesis in a child patient – Case report (Research, Society and Development, 2023)
Early Childhood Caries (ECC) is the presence of decayed, cavitated or not, missing or restored dental surfaces in children under 6 years of age. When neglected, it can lead to complications such as the loss of deciduous teeth, resulting in aesthetic and functional alterations that can be resolved with prosthetic oral rehabilitation in some cases. The objective of this study is to describe, through a case report, the aesthetic and functional rehabilitation with complete dentures, highlighting the importance of a multidisciplinary approach for the child's well-being. A 4-year-old male patient, weighing 10 kilograms, presented at the dental clinic of the Tiradentes University, accompanied by a guardian who reported chewing difficulties, weight loss, and difficulty with interpersonal interaction and socialization. Upon performing an intraoral clinical examination, premature tooth loss and various Dental Units (UDs) with a diagnosis of ECC were observed. Furthermore, a radiographic examination revealed extensive decay in UDs 53, 54, 55, 63, and 65. Extractions were performed, followed by the placement of a complete upper prosthetic oral rehabilitation. Therefore, this rehabilitation, despite being challenging, is crucial for maintaining oral health integrity. In cases of deciduous tooth destruction, it is used to improve masticatory, phonetic, and esthetic functions, providing a higher quality of life and social interaction for the child.